Cryptosporidiosis is predominantly an urban, anthroponotic infectious disease among Zambian children. (13th August 2021) - Banda, Barbara; Siwila, Joyce; Mukubesa, Andrew N; Chitanga, Simbarashe; Kaonga, Patrick; Changula, Katendi; Simulundu, Edgar; Saasa, Ngonda; Kelly, Paul
Abstract: Background: Cryptosporidium species are leading causes of diarrhoea in children and immunocompromised individuals. This study aimed to characterise Cryptosporidium species from children in rural and urban settings of Zambia. Methods: Stool samples collected from 490 children aged <5 y with diarrhoea were assessed for Cryptosporidium oocysts microscopically. A structured questionnaire was used to collect demographic and socioeconomic characteristics. Positive samples were subjected to PCR and gp60 sequence analysis. Results: The overall prevalence was 10% (50/490, 95% CI 7.8 to 13.2) with a peak in March, the late rainy season. Children who came from households where boiling water was not practised (OR=2.5, 95% CI 1.29 to 5.17; p=0.007) or who had experienced recurrent episodes of diarrhoea (OR=9.31, 95% CI 3.02 to 28.73; p=0.001) were more likely to have Cryptosporidium infection. Genotyping of 16 positive samples (14 from urban and 2 from rural sources) revealed Cryptosporidium hominis (14/16) and Cryptosporidium parvum (2/16). The Cryptosporidium hominis subtypes identified were Ia, Ib and Ie with subtype families IeAIIG3 (1), IbA9G3R2 (2), IaA31R3 (3), IbA9G3 (5), IaA27R3 (1), IaA30R3 (1) and Ia (1). Subtypes IbA9G3 and Ia were identified in children from a rural area. Cryptosporidium parvum subtypes were IIcA5G3R2 (1) and IIcA5G3a (1). Conclusions: All isolates successfully genotyped were C. hominis or anthroponotic C. parvum, suggesting that anthroponotic transmission dominates in Lusaka and the surrounding countryside.